Challenges of Da'wah Research: Understanding Da'wah Models in The Context of Qur'anic Guidance and Social Change - Muadz Abdus Salam; Andri Nirwana AN; Ainur Rhain; Alfiyatul Azizah; Yeti Dahliana; Ahmad Nurrohim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to investigate the challenges in understanding da'wah models in the context of Qur'anic guidance and social change. The lack of comprehensive research in this field has been a major obstacle in understanding the extent to which da'wah models conform to the teachings of the Qur'an. Problems such as inconsistencies in definitions and assessment parameters, limitations of empirical data, as well as gaps in understanding of Qur'anic guidance and integration of Qur'anic concepts in da'wah models are the main focus of this study. With the rapid pace of change in social and technological contexts, it is also necessary to understand how da'wah models can adapt to these changes while remaining in line with Qur'anic values. Advanced research in this field will provide a better understanding of how to practice da'wah in accordance with the guidance of the Qur'an, as well as the challenges and opportunities faced in the context of ongoing social change. In solving these problems, the author uses a qualitative approach, data is collected through documents and then the data is filtered and analyzed. The data analysis technique is carried out through the content analysis method. Based on the results of the study, it was found that there are various forms of technical words introduced by the Qur'an that are in line with the meaning of da'wah. The variety of words that have the same meaning as the meaning of da'wah can be understood that the Qur'an has such a rich vocabulary that the use of words is more diverse. In addition, in its implementation, da'wah can be seen from multiple points of view so that it must use words that are more in accordance with the human conditions faced. Among some specific criteria or characteristics that distinguish da'wah verses from other groups of verses are: da'wah verses contain basic norms that are global; contains elements of clear commandments (sharih al-amr) and prohibitions (sharih al-nahy); the connection of da'wah verses with matters of creed, morals, muamalah, including wa‟ad and wa‟id; and the da'wah verses in the Qur'an also use broad, flexible, firm and accurate language.